+0  
 
0
164
2
avatar

If h(z)=2z^2-5z+7, find h(3c)

Guest Mar 5, 2017
edited by Guest  Mar 5, 2017
 #1
avatar+7155 
+2

h(z) = 2z- 5z + 7

 

To find h(3c), replace each z with 3c.

h(3c) = 2(3c)2 - 5(3c) + 7

 

Now just simplify.

h(3c) = 2(9c2) - 5(3c) + 7

 

h(3c) = 18c2 - 15c + 7

hectictar  Mar 5, 2017
 #2
avatar
+5

Ohhhh ok thanks! That cleared it up I did the second step wrong

Guest Mar 5, 2017

7 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.